Pluralism as an antidote to epistemic violence in psychological research. (June 2020) - Novis-Deutsch, Nurit
The debate on objectivist versus relativist epistemologies in psychology and their relation to "othering" should consider a third stance that espouses epistemic pluralism. In order to understand the human experience, we must simultaneously explore the universal–humanistic, cultural, and idiographic aspects of the individual. Each of these aspects entails a different epistemic stance (objective, intersubjective, and subjective) and each assigns different meanings to "othering." In addition, a pragmatic epistemology that posits "progressivism" as its sole agenda risks the epistemic violence of discounting other sets of values and moral foundations that matter to many (often othered) people. Additional steps are needed in order to truly diversify psychological study.